Restoration of roof and ceiling / Muhammad Faiz Ahda Khairol - Khairol, Muhammad Faiz Ahda (Universiti Teknologi MARA, Perak, 2018)
Roof is a compulsory part of every building structure. It is beneficial in providing protection for the inside compartment of the building from any weather threat. When it has been used over many years, it is necessary to replace the roof if there are any defects happen. Thus, this report is written to show the overall restoration progress of roof structure. The objective of this report is to study the suitable method that can be used to renovate the roof according the guidelines. It is focusing on restoration works of roof structure and other related structure such as ceiling and rain water down pipe at the residencies area.